241 LEVELS OF SPO2 BETWEEN 85% AND 93% ARE ASSOCIATED WITH NORMOXEMIA IN NEWBORNS RECEIVING OXYGEN THERAPY (FIO2 > 0.21) IN THE NEONATAL INTENSIVE CARE UNIT. Issue 1 (1st January 2007) - Castillo, A.; Baquero, H.; Neira, F.; Alvis, R.; Critz, A.; Rogido, M.; Deulofeut, R.; Sola, A.
Abstract : Introduction: Newborns (NBs) breathing room air (RA) have normal SpO2 of 95 to 100% but keeping SpO2 95 to 100% in NB breathing FiO2 > 0.21 can cause hyperoxia. In 2003 and 2006, we reported that SpO2 85 to 95% is associated with less morbidity. There is concern that these SpO2 levels may cause persistent or intermittent hypoxemia. Objective: To evaluate PaO2 at different SpO2 levels in NBs with arterial catheters. Methods: Prospective comparison of PaO2 and SpO2 in stable NB in six NICUs located at sea level in two countries. PaO2 was obtained for clinical indications; simultaneous SpO2 was recorded at the time of the arterial gas. Comparisons were made only in stable NBs if the SpO2 changed < 1% before, during and after the collection of the sample. Statistics: Chi-square, Fishers, bivariate and multivariate analysis. Results: 674 paired SpO2 values in 85 NBs; 20% of the samples when NBs in RA. GA and BW: 30.5 ± 5.3 w and 1, 516 ± 910 g. NBs in RA: Mean and median SpO2 were 94.6% ± 4.3 and 96% (73-100%); with SpO2 85 to 93%, mean PaO2 was 59.4 ± 15.9 mm Hg. When SpO2 > 93%, mean PaO2 was 72.7± 24.7 mm Hg. NBs breathing FiO2 > 0.21: (a) With SpO2 85 to 93%, mean PaO2 was 60 ± 16.7 mm Hg, median 56 mm Hg (29-112); PaO2 of 40 to 80 mm Hg in > 79% of samples, and PaO2 < 40 mm Hg in 5%. (b) With SpO2 > 93%, mean PaO2 was 122.7 ± 62.9 mm Hg, median 110 mm Hg (38-438) (p ≤ .001 vs infants with SpO2 85-93%); 72% of the PaO2 values were > 80 mm Hg and 27% between 40 and 80 mm Hg. Conclusions: NBs breathing FiO2 > 0.21: (1) Normoxemia is much more frequent with SpO2 85 to 93% than with SpO2 > 93%; (2) SpO2 85 to 93% avoids abnormally high PaO2 and is infrequently associated with low PaO2 ; (3) SpO2 > 93% is associated with hyperoxia, which may be of risk in some NBs receiving FiO2 > 0.21.